Chagasic antibodies induce cardiac COX-2/iNOS mRNA expression with PGE2/NO production - Ganzinelli, Sabrina Belen (2009)
We demonstrate that serum IgG in chagasic patients interacting with the second extracellular loop of human cardiac M2 muscarinic acetylcholine receptors (M2 mAChR) trigger the production of PGE2 and NO, that in turn induces COX-2/iNOS mRNA expression. An association between serum anti-M2 peptide IgG, anti-cardiac membrane IgG and PGE2 levels (pb0.05) in chagasic dysautonomic patients was observed. Thus, we establish that serum anti-mAChR autoantibodies and PGE2 might be considered as early markers of Chagas´ associated dysautonomia. Affinity purified anti-M2 peptide IgG from chagasic sera, while stimulating myocardial M2 mAChR, it exerts an increase on PGE2 generation and NOS activity, as well as COX-2/iNOS isoforms mRNA expression. The expression of these genes is related with phosphoinositides (PIs), cGMP accumulation and PKC activity. Inhibition of these enzymes shows that chagasic autoantibodies upregulation of COX-2/iNOS mRNA level is under the control of endogenous iNO/cGMP signalling system. These results provide a novel insight into the role that cholinoceptor antibodies play in the development of myocardial inflammation. To our knowledge, there has been no previous report showing that an antibody interacting with heart mAChR can act as expression inducer of proinflammatory mediators.